Solar PV in the airport environment: a review of glare assessment approaches & metrics - S., Sreenath; K., Sudhakar; A. F., Yusop (Elsevier Ltd, 2021)
Solar photovoltaic technologies are increasingly implemented in airport premises. In certain conditions of sun path, the glare from solar photovoltaic modules may the reduce visibility of pilots and air traffic controllers. Despite the threat to aviation safety with solar installations in airport, only a few countries have framed regulation on glare impact. The paper attempts to study the various factors affecting the occurrence of glare from solar PV array in Airport. The main objective is to review the approaches and metrics for assessing the glare impact from the solar photovoltaic array. In addition, the work summarises the glare guidelines existing in USA, Canada and European nations. The main factors that influence the glare occurrence are suns position, tilt angle, Surface texture, color and location of PV module. It was concluded that the existing glare assessment approaches are of limited practical use in the worldwide scenario. Though there are several limitations with the existing glare indices, the Ho et al metrics is reasonably a good indicator for glare assessment in airport solar PV installations. Guidelines formulated by Federal Aviation Administration, (FAA), USA is good enough to be used as guideline for glare impact assessment in other countries. It is envisaged that this work will assist the research communities for the development of the globally acceptable glare assessment and metrics.